Tipo de incubadora e idade de matrizes sobre o rendimento de incubação e qualidade de pintainhos - Schadeck, Marli Marcondes (2020)
Genetic evolution has had a great impact on incubation, so interest in the ways of incubation has grown day by day. In this context, the objective of the research was to evaluate the type of incubator and the age of the hen on the incubation yield and chick quality. The experimental design was randomized in a bi-factorial arrangement. Factor A corresponded to the age of the mothers (33; 55; 63 weeks), and factor B corresponded to the type of incubator (single-stage; transformed single-stage; multiple stages), totaling nine treatments. According to the analysis of variance, there was an interaction between the factors analyzed on the variables blood vessels / cm (centímetro quadrado) (porcentagem), hatched eggs (porcentagem), salable chicks (porcentagem), chick length (cm) and liver weight (g). Both factors were significant, however, without interaction, on the variables, weight loss from the 1st to the 18th day (porcentagem) and average chick weight (g). For the variables heart weight (g) and weight of intestine (g), only the incubator factor was significant. For the variables number of pores/cm (centímetro quadrado), embryo mortality 1st phase and yolk sac weight (g) only the age factor of the matrix was significant. For the variables weight loss in transfer (porcentagem), contaminated eggs (porcentagem), embryo mortality 2°, 3° and 4° phase, and chicks eliminated (porcentagem) none of the factors was significant. For the variables live chickens and dead chickens (porcentagem) analyzed by the Kruskal-Wallis test (α = 0.05), it was possible to verify that there was no evidence of significant difference on the variables depending on the type of incubator and age of the hen. In general, in the present study it was observed that both factors analyzed affected the quality and well-being in the incubation process of hatching eggs. In the present study, it was possible to conclude that single stage incubators promote superior performance in embryo development until the formation of chicks, when compared to multiple stage incubators. It is possible to transform a multi-stage incubator so that it operates as a single-stage incubator, and obtain satisfactory results similar to that of a single stage. Still, regarding the age of the hens, it is possible to infer that younger hens stand out in most aspects assessed, often regardless of the incubation environment. While older hens depend on optimal conditions to present better results.